2021
DOI: 10.1038/s41598-021-88989-9
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage potentiates the recovery of liver zonation and metabolic function after acute liver injury

Abstract: The liver is an exclusive organ with tremendous regenerative capacity. Liver metabolic functions exhibit spatial heterogeneity, reflecting liver zonation. The mechanisms controlling the proliferation of hepatocytes and the accompanying matrix reconstruction during regeneration have been well explored, but the recovery potential of differentiated metabolic functions and zonation after liver injury remains unclear. We employed a mouse model of carbon tetrachloride (CCl4) induced-acute liver injury with clodronat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…Arginine supplementation is known to reduce liver injury [55,56]. The serum levels of arginine decrease in patients with acute liver injury [57,58]. Therefore, blood arginine is a good indicator of liver regeneration after acute liver damage [57][58][59].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Arginine supplementation is known to reduce liver injury [55,56]. The serum levels of arginine decrease in patients with acute liver injury [57,58]. Therefore, blood arginine is a good indicator of liver regeneration after acute liver damage [57][58][59].…”
Section: Discussionmentioning
confidence: 99%
“…The serum levels of arginine decrease in patients with acute liver injury [57,58]. Therefore, blood arginine is a good indicator of liver regeneration after acute liver damage [57][58][59]. These ndings suggest that arginine biosynthesis mediates the hepatoprotective effect of JGP.…”
Section: Discussionmentioning
confidence: 99%
“…17 Valine is a kind of branched-chain amino acid, which was reported to be crucial for the prevention of liver injury. 34,35 A recent study 36 demonstrated that Ganfule capsule (GFL) might play the protective effect on liver fibrosis by valine biosynthesis. Serine is important in cellular metabolic processes that link glycolysis with one-carbon metabolism to keep redox balance and proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…Upon removal, the liver and skeletal muscles of each rat were immediately fixed in 4% formaldehyde. After routine paraffin embedding, the sample was cut into 5 μ m sections and stained with periodic acid-silver (PAS) for the detection of histopathological alterations and glycogen changes [ 19 ].…”
Section: Methodsmentioning
confidence: 99%